2023
DOI: 10.1002/cam4.5418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics and outcomes of young‐onset versus average onset pancreatico‐biliary adenocarcinoma

Abstract: Background Young‐onset gastrointestinal malignancies appear to be increasing in incidence. There are limited data on young‐onset pancreaticobiliary adenocarcinoma (YO‐PBA). Methods The study comprised patients with PBA (pancreatic adenocarcinoma, intra‐, and extra‐hepatic cholangiocarcinoma) and included in the National Cancer Database (NCDB) between 2004 and 2017. YO‐PBA was defined as a diagnosis at age less than 50 years. Logistic regression to assess factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Given the prevalence of early-onset cancer and the extension of lifespan, heightened attention must be paid to early-onset cancers (22)(23)(24). The incidence of GEP-NENs has been increasing for decades worldwide (20).…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of early-onset cancer and the extension of lifespan, heightened attention must be paid to early-onset cancers (22)(23)(24). The incidence of GEP-NENs has been increasing for decades worldwide (20).…”
Section: Discussionmentioning
confidence: 99%
“…Details on trial designs, patient characteristics, study treatments, statistical assumptions, and outcome parameters can be found in Table 1 and Supplementary Table S1 , available at https://doi.org/10.1016/j.esmoop.2024.102944 , and the published original reports. 12 , 15 , 16 , 17 , 18 , 19 The overall recruiting period for these five studies was from December 1997 to January 2017. All analyses were carried out based on the respective intention-to-treat population.…”
Section: Methodsmentioning
confidence: 99%
“… 11 In addition, very little is known about whether the disease of younger patients with PDAC differs pathophysiologically from that of older patients. 12 Two recent publications have delved deeper into the hypothesis suggesting that younger patients with pancreatic and gastrointestinal cancers may exhibit distinct pathogenetic patterns in their tumors. Consequently, they might require more personalized treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 While most patients affected by BTC belong to older age groups (defined as 50 years or older), a disturbing trend is the increasing incidence of early-onset BTC (eoBTC; defined as cancers in patients younger than 50 years). [6][7][8] BTC, particularly the intrahepatic BTC and gallbladder cancers, has been identified as the cancer types with the highest rates of increase in incidence for early-onset cancers with annual percentage changes of 8% and 2%, respectively. 8 Several unique clinical characteristics such as advanced stage at presentation and refractoriness to chemotherapy have been described in eoBTC.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several unique clinical characteristics such as advanced stage at presentation and refractoriness to chemotherapy have been described in eoBTC. 6,9 BTC, up to 40%, do harbor targetable alterations, and molecular profiling for all patients is currently recommended by the National Comprehensive Cancer Network (category 2A). [12][13][14][15][16] However, most studies and clinical trials in BTC are based on the average age of onset.…”
Section: Introductionmentioning
confidence: 99%